Person’s Health Creation Potential as a Resource of Integrated Health - Anatoly G Madzhuga (Journal of Global Pharma Technology, 2017)
Introduction: The paper deals with the genesis of the notion of “potential”, offers a vector-contextual model of person’s health creation potential, and reveals psychological essence of the specified phenomenon. Basing on the results of empirical study, the authors prove that person’s health creation potential is a multidimensional structure integrating three factors – valeological mindset, metacognitive abilities, and affective self-attribution. For the first time, the paper represents the characteristic of resource provision of human health in the context of a holistic approach. Besides, it shows and scientifically justifies the structure of health creation potential, which acts as a mechanism of human self-cognition, self-evaluation, and self-development.Method: The authors use a method of vector modelling, which enables to create a vector-contextual model of person’s health creation potential. This model allows us to define milestones for elaborating and approving special impacts from pedagogues, parent, and administration, which provide the formation of the culture of learners’ health and their personal position concerning health creation.Results:A vector-contextual model of person’s health creation elaborated and conceptualized by the authors enables a pedagogue to forecast sustainable qualities of learners’ self-realizing creative personality and levels of its readiness to health creation activities in constantly changing conditions of society and environment. It plays a significant role in the development of human intelligence and creation and has an impact on the protection, formation, and strengthening of human health.Discussion or Conclusion: Basing on theoretical analysis of literature detoted to the topic of study, the authors represent a refined definition of “health creation potential” notion, design its vector-contextual model, and justify main components-vectors: valeological mindset, metacognitive abilities, and affective self-attribution in the structure of person’s health creation potential. In the context of the topic under study, the authors define conceptual-theoretical models of health-creation potential, which create perspectives for applied research in the methodology of theory of individual health and optimization of the process of actualization of health creation potential at various periods of ontogenesis. Keywords: Health, Vector-contextual model, Valeological mindset, Metacognitive abilities, Affective self-attribution, Health creation competence.